2014
DOI: 10.1002/j.2161-1912.2014.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

An “Afterthought”: Counseling Trainees’ Multicultural Competence Within the Spiritual/Religious Domain

Abstract: Although spiritual/religious identity development is included within multicultural training on the theoretical level, significant gaps exist in counseling trainees' practical preparation for spiritual/religious competence. This grounded theory study explores counseling trainees' multicultural counseling competence within the spiritual/religious domain. Findings reveal that although trainees participated in multicultural counseling preparation, they experienced spiritual/religious training as an "afterthought,"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Overall, the results of this survey reinforce recommendations for religious and spiritual topics to be explicitly integrated into professional counseling (e.g., Fukuyama & Sevig, ; Hage et al, ; Magaldi‐Dopman, ; T. B. Smith & Richards, ). In spite of the widely acknowledged concerns about religious proscriptions regarding sexuality (L. C. Smith & Okech, ; Whitman & Bidell, ) and other conduct, a counselor can openly speak of spiritual and religious diversity, just as issues of sexism, ableism, classism, and so on have been normalized in professional discourse without fears of adverse interpersonal or workplace repercussions.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Overall, the results of this survey reinforce recommendations for religious and spiritual topics to be explicitly integrated into professional counseling (e.g., Fukuyama & Sevig, ; Hage et al, ; Magaldi‐Dopman, ; T. B. Smith & Richards, ). In spite of the widely acknowledged concerns about religious proscriptions regarding sexuality (L. C. Smith & Okech, ; Whitman & Bidell, ) and other conduct, a counselor can openly speak of spiritual and religious diversity, just as issues of sexism, ableism, classism, and so on have been normalized in professional discourse without fears of adverse interpersonal or workplace repercussions.…”
Section: Discussionsupporting
confidence: 71%
“…If counselors preferred to address religion and spirituality as separate from multiculturalism, the topics of religion and spirituality would likely not be meaningfully integrated into the profession at all. Although scholars call for additional attention to those topics (Adams et al, ; Cashwell & Bartley, ; Hage et al, ; Hull, Suarez, & Hartman, ; Magaldi‐Dopman, ; Young et al, ), the reality is that publicly funded colleges and counseling centers unaffiliated with a religious institution will not invest in those topics, given the other aspects of diversity that clamor for attention, time, and resources. Multiculturalism is already integral to our profession (Ratts et al, ), and no framework besides multiculturalism would or could inform the entire counseling profession about religious and spiritual diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is essential that supervisors continue to assess, support, and challenge supervisees throughout their professional preparation. Although various forms of identity are interwoven into many counselor education courses, they are done mostly on a theoretical level, leaving significant gaps in counseling trainees' practical preparation for identity and value integration (Magaldi‐Dopman, ; Minnix, ).…”
Section: Implications For Counselor Educators and Supervisorsmentioning
confidence: 99%
“…A major theme that emerges across the literature is the lack of training for clinicians to implement religion and spirituality into counseling (Adams, 2012;Burke, Hackney, Hudson, Miranti, Watts, & Epp, 1999;Hall, Dixon, & Mauzey, 2004;Magaldi-Dopman, 2014;Saunders, Petrik, & Miller, 2013;Walker, Gorsuch, & Tan, 2004;Wiggins-Frame, & Cashwell, 2007;Young, van Asselt, & Senstock, 2009;). The seminal work of Kelly (1994) found that only 25% of the 341 schools surveyed included religious and spiritual issues as course components.…”
Section: Religion and Spirituality In Trainingmentioning
confidence: 99%